Direct Scaffolding of Biomimetic Hydroxyapatite-gelatin Nanocomposites using Aminosilane Cross-linker for Bone Regeneration - Chiu, Chi-Kai (2012)
Hydroxyapatite-gelatin modified siloxane (GEMOSIL) nanocomposite was developed by coating, kneading and hardening processes to provide formable scaffolding for alloplastic graft applications. The present study aims to characterize scaffolding formability and mechanical properties of GEMOSIL, and to test the in vitro and in vivo biocompatibility of GEMOSIL. Buffer Solution initiated formable paste followed by the sol-gel reaction led to a final hardened composite. Results showed the adequate coating of aminosilane, 11–19 wt%, affected the cohesiveness of the powders and the final compressive strength (69 MPa) of the composite. TGA and TEM results showed the effective aminosilane coating that preserves hydroxyapatite-gelatin nanocrystals from damage. Both GEMOSIL with and without titania increased the mineralization of preosteoblasts in vitro. Only did titania additives revealed good in vivo bone formation in rat calvarium defects. The scaffolding formability, due to cohesive bonding among GEMOSIL particles, could be further refined to fulfill the complicated scaffold processes.